Site-specific author's drama - Strejčková, Hana (Amfiteater (Ljubljana), 2022)
The article discusses the role of the playwright in contemporary site-specific drama and the role of the director of site-specific performance. The study aims at three main areas: the author’s drama based on the recent history of the 20 th century; the performative potential of the commonness and of oral history; and contemporary site-specific drama. As a playwright, the author focuses on the memories of witnesses and socially taboo topics. As a theatre director, she examines approaches for transforming into theatrical language the memory of place, the collection of data from oral history and burning issues. She looks at the relations between playwrights and site-specific performance. She observes the links among the topic, communication means and non-theatrical places. This qualitative longitudinal art research is based on experience from theatre practice, analysis and comparison of theoretical knowledge. The author gives examples of authorial plays and reports on their productions, specifically stating these dramas: Midnight in the Borderland (3. /4. 5. 1950, a monastery), Three Chairs (Alzheimer’s disease, a retirement home), From Majdalenka to Madla (World War II, cellar), Hotel on the Corner (1932–1989, old theatre building). The study emphasises the need for a creative and attentive approach by the author, playwright, dramaturg and director to create a whole new world from the duality: ordinary and taboo. It turns out that the combination of a strong theme, an unusual place tied to the topic of the drama, and the participatory role (active/passive) of the audience can be an effective strategy and even “tactic” in strengthening the role of the author in drama after the year 2000.
Keywords: ambientalna drama; author's drama; avtorska drama; dramatiki; oral history; playwriting; site-specific drama; ustna zgodovina